T5 The KCa3.1 K+ channel mediates wound healing in human myofibroblasts. (2nd December 2011) - Roach, K M; Coward, W; Feghali-Bostwick, C; Duffy, S M; Bradding, P
Abstract : Idiopathic pulmonary fibrosis (IPF) is a common progressive interstitial lung disease and current treatments are ineffective. The Ca 2+ -activated K + channel KCa 3.1 modulates the activity of several structural and inflammatory cells which play important roles in model diseases characterised by tissue remodelling and fibrosis. We hypothesise that KCa 3.1-dependent cell processes are a common denominator in IPF. We have therefore examined KCa 3.1 expression and function in human myofibroblasts derived from patients with IPF and non-fibrotic controls (NFC). IPF tissue was obtained from diagnostic lung biopsies, and NFC tissue from healthy lung removed at surgery for carcinoma. Myofibroblasts grown in vitro were characterised by Western blot, immunofluorescence and RT-PCR to determine KCa 3.1 channel expression. Patch clamp electrophysiology was used to demonstrate functional KCa 3.1 channels. Wound healing and proliferation assays were performed using two specific KCa 3.1 blockers (TRAM-34, ICA-17043 [Senicapoc]). Both NFC and IPF myofibroblasts expressed KCa 3.1 channel mRNA and protein. Using the KCa 3.1 channel opener 1-EBIO, KCa 3.1 ion currents were elicited in 59% of NFC and 77% of IPF myofibroblasts tested (p=0.0411). These currents were blocked by TRAM-34 (200 nM). The 1-EBIO-induced currents were significantly larger in IPF cells compared to NFC cells (p=0.0124). Basic fibroblast growth factor (bFGF) (10 ng/ml) significantly increased the frequency of KCa 3.1 currents across groups (p=0.0046). Similarly bFGF stimulation significantly increased myofibroblast wound healing (p=0.002). Following KCa 3.1 blockade bFGF-stimulated wound healing was attenuated dose-dependently. Thus at the 48 h time-point wound healing was reduced by 22.2±11.1% and 27.3±9.5% for TRAM-34, 20 nM and 200 nM respectively (p=0.0467 across groups), and reduced by 16.9±8.1% and 24.4±6.6% for ICA-17043, 10 nM and 100 nM respectively (p=0.0076 across groups). KCa 3.1 blockade had no effect on myofibroblast proliferation. We show for the first time that human lung myofibroblasts express the KCa 3.1 K + channel. KCa 3.1 currents are larger and more frequently present in cells from patients with IPF, and functional channel expression is increased by pro-fibrotic growth factors. KCa 3.1 inhibition attenuates bFGF stimulated myofibroblast wound healing. These findings raise the possibility that blocking the KCa 3.1 channel will inhibit pathological myofibroblast function in IPF, and thus offer a novel approach to IPF therapy.